LGG-22. SJ901: Phase I/II evaluation of single agent mirdametinib (PD-0325901), a brain-penetrant MEK1/2 inhibitor, for the treatment of children, adolescents, and young adults with low-grade glioma (LGG). (3rd June 2022) - Vinitsky, Anna; Chiang, Jason; Bag, Asim K; Campagne, Olivia; Stewart, Clinton F; Dunphy, Paige; Shulkin, Barry; Li, Qian; Lin, Tong; Hoehn, Mary Ellen; Johnson, Jason N; Towbin, Jeffrey A; et al.
Abstract: BACKGROUND: MEK inhibitor trials in pediatric low-grade glioma (pLGG) have yielded promising results, but there remains room for improvement since objective responses are rarely complete and disease recurrence after completion of therapy is common. Mirdametinib (PD-0325901) is a highly selective MEK1/MEK2 inhibitor that, in preclinical studies, has been reported to have superior blood-brain-barrier penetration compared to other MEK inhibitors. As such, we recently launched the SJ901 clinical trial (NCT04923126) to determine the safety, recommended phase 2 dose, pharmacokinetics, and preliminary efficacy of mirdametinib in patients with pLGG when administered continuously. Here, we present preliminary phase 1 data. METHODS: SJ901 is a multi-arm phase I/II trial of mirdametinib in patients >2 and <25 years with LGG. Phase I requires participants to have no prior exposure to MEK inhibitors and recurrent/progressive disease with biopsy-proven evidence of MAPK pathway activation. Three escalating dose levels (2 mg/m2/dose BID, 2.5mg/m2/dose BID and 3mg/m2/dose BID) are planned using a rolling 6 design. RESULTS: Accrual began in June 2021. As of Jan 13, 2022, eleven patients enrolled: 5 on dose level 1 (DL1) and 6 on dose level 2 (DL2). Median age is 10 (3-21) years. Ten patients have somatic gene rearrangements (7 BRAF, 1 MYB, 1 RAF1, 1 FGFR1) and one has an NF1 germline mutation. Four have metastatic disease. No dose-limiting toxicities occurred for DL1 (whereas data are pending for DL2) and only grade 1/2 treatment-related adverse events have been observed. No MEK-related retinopathy or cardiopathy has been observed. Four of the six patients with at least one follow-up disease evaluation have a minor response (>25%-<50% decrease). Median time on therapy is 6.6 (2.2-7) months. No disease progressions have occurred. CONCLUSION: Thus far, mirdametinib is well-tolerated and clinically promising when dosed continuously in patients with recurrent/progressive pLGG. More information will be forthcoming.